Health Belief Model on the Predictors of Healthy Sex Behavior among Commercial Female Sex Workers in Surakarta, Central Java - Syarifah Syarifah; Argyo Demartoto; Ruben Dharmawan (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Sexually transmitted infections (STIs) are diseases that are now a global issue because they are the entrance to HIV transmission. Female sex workers (WPS) have a high risk of contracting and transmitting STIs and HIV / AIDS due to unsafe sex behavior. The purpose of this study was to analyze the relationship of safe sex behavior for the prevention of sexually transmitted infections in female sex workers in Surakarta.Subjects and Method: A cross-sectional study was conducetd in Surakarta, Central Java, from December 2017 to January 2018. A sample of 105 female sex workers was selected by fixed disease sample. The dependent variable was safe sex behavior. The independent variables were perceived susceptibility, perceived seriousness, perceived benefit, perceived barrier, perceive threat, cues to action, and self-efficacy. The data were collected by questionnaire and analyzed by a multiple logistic regression.Results: Safe sex behavior among female sex worker increased with strong perceived benefit (b= 0.18; 95% CI= 0.74 to 0.28; p= 0.001) and strong self-efficacy (b=0.51; 95% CI=0.25 to 0.76; p<0.001). Safe sex behavior decreased with strong perceived barrier (b= 0.15; 95% CI= -0.27 to